Hasil Tebu Pertama dan Keprasan serta Efisiensi Penggunaan Hara N dan S akibat Substitusi Amonium Sulfat - Nurhidayati, ,; Basit, Abdul; Sunawan, , (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2013)
This study was aimed to describe the substitution of ammonium sulfate (AS) with the other fertilizers containing theequal N and S to the cane and sugar yield and nutrient use efficiency of the plant and ratoon cane. A field experiment with arandomized complete block design and three replications was conducted on the dry land in two consecutive cropping seasonsof 2010 to 2011. There were 10 treatments consisting of three treatments tested using the AS fertilizer, three treatments usingAS substitute in the form of urea + gypsum, three treatments using AS substitute in the form of urea + gypsum + biocompostand a control treatment (without fertilizer). The results showed that for the plant cane, the highest cane yield was obtainedon the treatments using urea + gypsum, while the highest sugar content and yield on the treatment using urea + gypsum +biocompost with 140 kg N ha-1+168 kg S ha-1 rates. The highest nutrient use efficiency was obtained on the treatment using urea + gypsum 100 kg N ha-1+120 kg S ha-1 rates. For the ratoon cane, the highest cane yield, sugar content and yieldwere obtained in the treatment using urea + gypsum + biocompost. The highest nutrient use efficiency was obtained onthe treatment using urea + gypsum with 100 kg N ha-1+120 kg S ha-1 rates and urea + gypsum + biocompost with 140 kg Nha-1+168 kg S ha-1 rates. The range of the average increase in the nutrient use efficiency of substitution fertilizer between42-44% compared to the AS fertilizer. This results suggests AS fertilizer in sugarcane cultivation can be substituted with theother fertilizers which have equal N and S content.Keywords: AS fertilizer, AS substitution, cane and sugar yield, nutrient use efficiency